Identifying sources of support and barriers to physical activity in pediatric type 1 diabetes. Issue 1 (6th November 2019) - Livny, Ruth; Said, Wasim; Shilo, Smadar; Bar‐Yoseph, Ronen; Gal, Shoshana; Oren, Meirav; Levy, Milana; Weiss, Ram; Shehadeh, Naim; Zuckerman‐Levin, Nehama; Cohen, Michal
Abstract: Objectives: Reports suggest that children with type 1 diabetes (T1D) perform less than the recommended daily activity and are less active than their non‐diabetic peers. We aimed to: (a) Identify barriers and sources of support for exercise performance in pediatric T1D. (b) Identify strengths and limitations in the exercise‐directed education provided by our diabetes team. Methods: Patients with T1D 5 to 20 years of age were recruited while attending a routine clinic visit. Participants completed a set of questionnaires assessing demographics, health data, barriers, and sources of support for exercise performance and diabetes related exercise education. The clinics' medical staff filled‐out a questionnaire assessing the exercise‐directed education provided in clinic. Results: Ninety‐six subjects were included in this study, mean age 13.7 ± 3.8 years. Median weekly reported exercise time was 3.5 hours. The two most prevalent barriers were fear of hypoglycemia and low fitness, reported by 76% and 51%, respectively. Mean family and social support scores were 4.1 ± 0.7 and 3.3 ± 1.1, respectively (1‐5 scale); the latter correlated with the amount of activity performed (cc = 0.360; P < .001). The majority of participants (97%) reported receiving guidance for physical activity, to their satisfaction. Yet, knowledge and implementation were suboptimal. All staff members reported conducting routine exercise‐directed teaching, with variations in frequency and content. Conclusions: Our findings suggest that in order to increase the amount of safely performed exercise in pediatric patients with T1D, fear of hypoglycemia must be addressed. Further efforts should focus on: (a) encouraging active family and social involvement (b) standardization of education.